2011
DOI: 10.1074/jbc.m110.152405
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Inhibits Osteoclastogenesis and Bone Resorption via APPL1-mediated Suppression of Akt1

Abstract: Adiponectin is an adipokine playing an important role in regulating energy homeostasis and insulin sensitivity. However, the effect of adiponectin on bone metabolism shows contradictory results according to different research studies. In this study femurs were isolated from genetically doublelabeled mBSP9.0Luc/␤-ACT-EGFP transgenic mice and were transplanted into adiponectin knock-out mice or wild type mice to investigate the effect of temporary exposure to adiponectin deficiency on bone growth and metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 64 publications
(90 reference statements)
10
93
0
Order By: Relevance
“…We thus focused on investigating whether C/EBP␣ could activate the Akt signaling pathway in OC precursors, which has also been reported to be a strong regulator of OC survival (54 -57). We revealed that C/EBP␣ can induce Akt activation to promote OC survival (58,59). Importantly, this finding also suggests that a threshold level of C/EBP␣ may be required for effective Akt activation and that a drastic increase in C/EBP␣ expression may not substantially enhance Akt activation by RANKL.…”
Section: Discussionmentioning
confidence: 61%
“…We thus focused on investigating whether C/EBP␣ could activate the Akt signaling pathway in OC precursors, which has also been reported to be a strong regulator of OC survival (54 -57). We revealed that C/EBP␣ can induce Akt activation to promote OC survival (58,59). Importantly, this finding also suggests that a threshold level of C/EBP␣ may be required for effective Akt activation and that a drastic increase in C/EBP␣ expression may not substantially enhance Akt activation by RANKL.…”
Section: Discussionmentioning
confidence: 61%
“…peripheral blood mononuclear cells (PBMC), mouse primary bone marrow cultures and in RAW264.7 cells [38,43,48,60,61]. Only some of these studies mention the use of columns to remove LPS contamination or show that the effects were dependent on AdipoR1 [59,60].…”
Section: The Effects Of Adiponectin On Osteoclast Formation and Activitymentioning
confidence: 98%
“…One of the challenges of knockout animal studies is the adaption and compensation mechanisms that can sometimes mask the initial effect of the deficiency and lead to mistaken conclusions about the physiological role of the absent protein. An interesting approach aimed to overcome these challenges was used by Tu et al [48] who used femur explants from 3-day-old mice that were transplanted into APN-KO and WT controls and studied the effect of a transient exposure to adiponectin deficiency on bone growth and metabolism. The growth of bone explants was significantly retarded in the APN-KO mice in comparison with WT controls.…”
Section: Studies In Adiponectin-knockout Micementioning
confidence: 99%
“…Adiponectin is one of the adipokines that is produced in adipose tissue and regulates energy homeostasis and insulin sensitivity. Several studies indicate that adiponectin increases osteoclast apoptosis and decreases proliferation of osteoclast precursor cells (29,30). Leptin, a circulating hormone produced by adipose tissue, is a multifunctional hormone that plays important roles in body weight homeostasis, neuroendocrine function, fertility, immune function, and angiogenesis (31).…”
Section: Discussionmentioning
confidence: 99%